Mexico's drug war and criminal networks: the dark side of social media - Garcia, Nilda M. (Routledge advances in international relations and global politics, 2020)
"Mexico's Drug War and Criminal Networks examines the effects of technology on three criminal organizations: the Sinaloa cartel, the Zetas, and the Caballeros Templarios. Using social network analysis, and analyzing the use of web platforms Facebook, Twitter, and YouTube, Nilda M. Garcia provides fresh insights on the organizational network, the central nodes, and the channels through which information flows in these three criminal organizations. In doing so, she demonstrates that some drug cartels in Mexico have adopted the usage of social media into their strategies, often pursuing different tactics in the search for new ways to dominate. She finds that the strategic adaptation of social media platforms has different effects on criminal organization's survivability. When used effectively, coupled with the adoption of decentralized structures, these platforms do increase a criminal organization's survival capacity. Nonetheless, if used haphazardly, it can have the opposite effect. Drawing on the fields of criminology, social network analysis, international relations, and organizational theory and featuring a wealth of information about the drug cartels themselves, Mexico's Drug War and Criminal Networks will be a great source for all those interested in the presence, behavior, purposes, and strategies of drug cartels in their forays into social media platforms in Mexico and beyond"--